Gestión financiera y la toma de decisiones gerenciales en la empresa comercializadora San Juan SAC, periodo 2023 - Pezo Huaman, Carla Thais (2023)
Financial management are all those actions that the company develops in relation to the administration and control of its financial resources, and in which way they can be used appropriately for the fulfillment of the established goals and objectives, however, it is important to point out that these actions have to be evaluated so that management can make the best decisions aimed at generating the highest possible profitability. The research is entitled "Financial Management and Management Decision Making in the company Comercializadora San Juan SAC, period 2023", its objective is to determine the relationship between financial management and decision making for the aforementioned period. His study was of a quantitative type and a descriptive correlational design, using the survey as a technique and the questionnaire of questions as a data collection instrument, this being validated through the judgment of three experts who approved its application to 25 workers. Finally, the data were processed and analyzed using the statistical software spss v25 and as a result it was found that there is a considered positive relationship, which is supported by Spearman's Rho coefficient, which was 0.615 and the degree of significance at 0.001.